2011
DOI: 10.1128/aem.01581-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of Real-Time PCR Assays for Detection and Quantification ofBacillus cereusGroup Species: Differentiation ofB. weihenstephanensisand RhizoidB. pseudomycoidesIsolates from Milk

Abstract: Quantitative real-time PCR (qRT-PCR) offers an alternative method for the detection of bacterial contamination in food. This method provides the quantitation and determination of the number of gene copies. In our study, we established an RT-PCR assay using the LightCycler system to detect and quantify the Bacillus cereus group species, which includes B. cereus, B. anthracis, B. thuringiensis, B. weihenstephanensis, B. mycoides, and B. pseudomycoides. A TaqMan assay was designed to detect a 285-bp fragment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…MAA is the only acute phase protein produced in response to bacterial infection in the udder and is therefore an immediate and direct indicates of infection [93]. PCR (polymerase chain reaction) is used for bacteria identification and differentiation [94,95]. Gas chromatography/mass spectrometry can be used for analysis for metabolomics characterization of milk [96,97].…”
Section: Industry 40 In the Dairy Industrymentioning
confidence: 99%
“…MAA is the only acute phase protein produced in response to bacterial infection in the udder and is therefore an immediate and direct indicates of infection [93]. PCR (polymerase chain reaction) is used for bacteria identification and differentiation [94,95]. Gas chromatography/mass spectrometry can be used for analysis for metabolomics characterization of milk [96,97].…”
Section: Industry 40 In the Dairy Industrymentioning
confidence: 99%
“…Other primers and probes targeting the chromosome have been designed for specific detection and quantification of the Bcg as well as differentiation among Bcg species (43,44). However, our BLAST similarity searches on WGS databases in NCBI revealed that these Bcg primers missed a certain proportion of Bcg strains whose genome sequences have been published recently (22 April 2015) (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…d) were 0.9985 and 0.9992, respectively. These linear relationships indicate that the Ct values are a reliable basis for estimating the gene concentrations (Oliwa‐Stasiak et al ., ).…”
Section: Resultsmentioning
confidence: 97%